Immune response of human cultured cells towards macrocyclic Fe2PO and Fe2PC bioactive cyclophane complexes - Alex J. Salazar-Medina; Enrique F. Velazquez-Contreras; Rocio Sugich-Miranda; Hisila Santacruz; Rosa E. Navarro; Fernando Rocha-Alonzo; Maria A. Islas-Osuna; Patricia L. Chen; Sarah G.B. Christian; Amelia A. Romoser; Scott V. Dindot; Christie M. Sayes; et al. (PeerJ, 2020)
Synthetic molecules that mimic the function of natural enzymes or molecules have untapped potential for use in the next generation of drugs. Cyclic compounds that contain aromatic rings are macrocyclic cyclophanes, and when they coordinate iron ions are of particular interest due to their antioxidant and biomimetic properties. However, little is known about the molecular responses at the cellular level. This study aims to evaluate the changes in immune gene expression in human cells exposed to the cyclophanes Fe2PO and Fe2PC. Confluent human embryonic kidney cells were exposed to either the cyclophane Fe2PO or Fe2PC before extraction of RNA. The expression of a panel of innate and adaptive immune genes was analyzed by quantitative real-time PCR. Evidence was found for an inflammatory response elicited by the cyclophane exposures. After 8 h of exposure, the cells increased the relative expression of inflammatory mediators such as interleukin 1; IRAK, which transduces signals between interleukin 1 receptors and the NFκB pathway; and the LPS pattern recognition receptor CD14. After 24 h of exposure, regulatory genes begin to counter the inflammation, as some genes involved in oxidative stress, apoptosis and non-inflammatory immune responses come into play. Both Fe2PO and Fe2PC induced similar immunogenetic changes in transcription profiles, but equal molar doses of Fe2PC resulted in more robust responses. These data suggest that further work in whole animal models may provide more insights into the extent of systemic physiological changes induced by these cyclophanes.